2017
DOI: 10.1016/j.devcel.2017.08.002
|View full text |Cite
|
Sign up to set email alerts
|

YAP/TAZ Orchestrate VEGF Signaling during Developmental Angiogenesis

Abstract: Vascular endothelial growth factor (VEGF) is a major driver of blood vessel formation. However, the signal transduction pathways culminating in the biological consequences of VEGF signaling are only partially understood. Here, we show that the Hippo pathway effectors YAP and TAZ work as crucial signal transducers to mediate VEGF-VEGFR2 signaling during angiogenesis. We demonstrate that YAP/TAZ are essential for vascular development as endothelium-specific deletion of YAP/TAZ leads to impaired vascularization a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
306
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 298 publications
(323 citation statements)
references
References 63 publications
15
306
2
Order By: Relevance
“…Transcriptome and proteome data identified 7 overrepresented signaling pathways in normal diabetic mucosa that have been previously associated with tumor development: MAPK, Rap1, VEGF, Wnt, TGF‐β, Hippo, and Notch signaling pathways. These pathways regulate common downstream effectors that control downstream transcriptomic programs that promote carcinogenesis (Hiemer et al ., ; Hong et al ., ; Konsavage et al ., ; Slemmons et al ., ; X. Wang et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Transcriptome and proteome data identified 7 overrepresented signaling pathways in normal diabetic mucosa that have been previously associated with tumor development: MAPK, Rap1, VEGF, Wnt, TGF‐β, Hippo, and Notch signaling pathways. These pathways regulate common downstream effectors that control downstream transcriptomic programs that promote carcinogenesis (Hiemer et al ., ; Hong et al ., ; Konsavage et al ., ; Slemmons et al ., ; X. Wang et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…In view of our results, we selected specific targets to confirm hyperglycemia influence. Many evidences suggested a role in cancer initiation of the protein complex YAP/TAZ‐TEAD (Zanconato et al ., ) including several signaling pathways that we found altered in normal diabetic mucosa: MAPK (Hong et al ., ), VEGF (X. Wang et al ., ), Wnt (Konsavage et al ., ), TGF‐β (Hiemer et al ., ), or the Notch pathway (Slemmons et al ., ). We observed activation of the YAP/TAZ‐TEAD axis under hyperglycemic conditions in the assay of cultured normal colon epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, modulation of transcriptional factors that participate in controlling the expression of angiogenic factors has emerged as a promising strategy in antiangiogenic therapy. Recently, it has been revealed that transcriptional factor YAP acts as a potent mediator of angiogenesis in response to VEGF (Wang et al, ). In this study, we demonstrated that GA directly targeted YAP especially alleviated its nuclear expression and subsequently resulted in the inactivation of downstream STAT3, by which tumor angiogenesis was limited and tumor progression was prevented (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, recent studies have indicated that the Hippo-pathway facilitates mitochondrial function via Bcl-xL [24], demonstrating a possible relationship between Yap and cytoplasmic mitochondria. Furthermore, accumulating evidence has described the regulatory action of Yap on JNK [25, 26]. Thus, together with the confirmed role of JNK in initiating mitochondrial fission [27], these findings raise the possibility that Yap may govern mitochondrial fission via JNK.…”
Section: Introductionmentioning
confidence: 89%